Relationship between trajectory of changing in sexual partner numbers and early negative experiences among young men who have sex with men: a follow-up study - Huihao WANG; Bin YU; Liang YUAN; Xin LIU; Yue GUAN; Mengxi ZHAI; Jiayu LI; Hong YAN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine changes in the number of sexual partners among young men who have sex with men (YMSM) and their associations with early negative experiences (including adverse childhood experience [ACE] and the age of having first homosexual behavior). MethodsTotally 423 YMSM at ages of 16 - 24 years were recruited with accidental sampling and respondent-driven sampling during September 2017 - January 2018 with the assistance of gay men's organizations in three cities (Wuhan, Changsha and Nanchang) and were followed up three times from July 2018 to December 2020. Three subgroups of YMSM with different trajectories of changing in the number of sexual partners were discriminated through latent class trajectory modeling with the R LCTMtools program and the relationship between early negative experiences and the trajectory of changing number of sexual partners among the YMSM was explored using unordered multinomial logistic regression analysis. ResultsThe three types of trajectory of changing in the number of sexual partners discriminated among the YMSM were less fluctuation with small number, slow downward, and rapid upward and the proportion (number) of the YMSM assigned into the three trajectory subgroups were 46.81% (198), 35.70% (151), and 17.49% (74), respectively. Among the YMSM, 29.79% (126) reported the first homosexual behavior at the age of less than 18 years and 56.26% (238) reported ACE. The experiences of abuse, neglect, and family dysfunction were reported by 38.53% (163), 22.46% (95), and 27.66% (117) of the YMSM. Unordered multinomial logistic regression analysis revealed that after adjusting for potential confounders (age, education, occupation and sexual orientation) and compared to the YMSM of the subgroup with the trajectory of less fluctuation of small sexual partner number, the YMSM having first homosexual behavior under age of 18 years were more likely to have a slow downward trajectory (adjusted odds ratio [aOR] = 2.469, 95% confidence interval [95%CI]: 1.468 - 4.151) and a rapid upward trajectory (aOR = 2.565, 95%CI: 1.360 - 4.838) of sexual partner number; the YMSM ever experiencing physical abuse and sexual abuse were more likely to have a slow downward trajectory, with the aORs (95%CI) of 1.943 (1.003 - 3.765) and 1.854 (1.053 - 3.265); and the YMSM ever experiencing physical abuse were more likely to have a rapid upward trajectory (aOR = 2.386, 95%CI: 1.114 - 5.108). ConclusionThe self-reported early negative experience is high among YMSM recruited in three China cities and the trajectory of change in sexual partner number of the YMSM is associated with early negative experiences. The results suggest that attention should be paid to early negative experiences of YMSM for implementing relevant interventions.